The MHC Class Ia Genes in Chenfu’s Treefrog (Zhangixalus chenfui) Evolved via Gene Duplication, Recombination, and Selection - Hu Chen; Siqi Huang; Ye Jiang; Fuyao Han; Qingyong Ni; Yongfang Yao; Huailiang Xu; Sudhanshu Mishra; Mingwang Zhang (Animals, 2019)
The molecular mechanisms underlying the evolution of adaptive immunity-related proteins can be deduced by a thorough examination of the major histocompatibility complex (MHC). Currently, in vertebrates, there is a relatively large amount of research on MHCs in mammals and birds. However, research related to amphibian MHC genes and knowledge about the evolutionary patterns is limited. This study aimed to isolate the MHC class I genes from Chenfu’s Treefrog (Zhangixalus chenfui) and reveal the underlying evolutionary processes. A total of 23 alleles spanning the coding region of MHC class Ia genes were identified in 13 individual samples. Multiple approaches were used to test and identify recombination from the 23 alleles. Amphibian MHC class Ia alleles, from NCBI, were used to construct the phylogenetic relationships in MEGA. Additionally, the partition strategy was adopted to construct phylogenetic relationships using MrBayes and MEGA. The sites of positive selection were identified by FEL, PAML, and MEME. In Chenfu’s Treefrog, we found that: (1) recombination usually takes place between whole exons of MHC class Ia genes; (2) there are at least 3 loci for MHC class Ia, and (3) the diversity of genes in MHC class Ia can be attributed to recombination, gene duplication, and positive selection. We characterized the evolutionary mechanisms underlying MHC class Ia genes in Chenfu’s Treefrog, and in so doing, broadened the knowledge of amphibian MHC systems.